1991
DOI: 10.1002/arch.940180410
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria‐induced protein P4 (hemolin) from Manduca sexta: A member of the immunoglobulin superfamily which can inhibit hemocyte aggregation

Abstract: The synthesis of a number of hemolymph proteins is induced in insects in response to bacterial infections. The major induced hemolymph protein in larvae of Manduca sexta is a glycoprotein of Mr = 48,000 known as P4. We have isolated a clone for P4 from a fat body cDNA library constructed from RNA isolated from larvae injected with bacteria. The cDNA has an open reading frame encoding a 411 residue polypeptide with a hydrophobic NH2-terminal sequence, which appears to be a signal peptide. Analysis of the deduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 41 publications
3
78
0
1
Order By: Relevance
“…This may be an important alternative method of reducing pathogen-generated damage if molecules such as GSH are unavailable. Hemolin is a much larger molecule than GSH (it contains 411 amino acids, including several that contain sulphur; Ladendorff and Kanost, 1991), but it may be less likely to dampen early immune responses than GSH. The changes in hemolin and GSH may reflect network changes designed to both enhance PO activity and to mitigate some of the costs due to damage.…”
Section: Discussionmentioning
confidence: 99%
“…This may be an important alternative method of reducing pathogen-generated damage if molecules such as GSH are unavailable. Hemolin is a much larger molecule than GSH (it contains 411 amino acids, including several that contain sulphur; Ladendorff and Kanost, 1991), but it may be less likely to dampen early immune responses than GSH. The changes in hemolin and GSH may reflect network changes designed to both enhance PO activity and to mitigate some of the costs due to damage.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolin is a bacteria-inducible immunoglobulinlike protein whose role in insect immunity has been better studied. In the last 2 decades, independent studies have demonstrated that hemolin proteins are multifunctional molecules involved in a diverse range of cell interaction and are able to (a) bind lipopolysaccharides and be up-regulated in hemolymph during infections (15)(16)(17); (b) be up-regulated during metamorphosis (18,19); (c) promote opsonin-like effects, such as increased cell adhesion and phagocytosis (20,21); (d) agglutinate bacterial cells (17,22); (e) bind to hemocytes and inhibit their aggregation (15,20,22,23); and (f) regulate embryonic development (24,25).…”
mentioning
confidence: 99%
“…This molecule belongs to the IgSF and seems to be involved in the immune recognition process (Andersson & Stainer 1987;Sun et al 1990;Ladendorff et al 1991;Schmidt et al 1993). A homologue of human Down syndrome cell adhesion molecule (DSCAM) belonging to IgSF has been found in Drosophila.…”
Section: Insect Igsfmentioning
confidence: 99%